Influential families and Ottoman authority in southern Constantine: balances of power and conflict during the 18th-19th centuries - Hayet , Chibani; Abdelkamel, Attia (Journal of Ecohumanism, 2025)
This study explores the relationship between influential families and the Ottoman central authority in the Southern Beylik of Constantine during the 18th and 19th centuries. It examines the balance of power, influence, and conflict that shaped political and social life in the region. The study highlights how local notable families relied on tribal, economic, and religious influence to strengthen their authority, making them both partners and rivals of the Ottoman administration. It also analyzes the strategies adopted by the Ottoman Authority to control the region through alliances, administrative appointments, and military interventions. The research concludes that the relationship between both sides was dynamic, fluctuating between cooperation and conflict according to political and economic circumstances, which significantly influenced the political and social structure of Southern Constantine during the late Ottoman period.